Tindak Tutur Ilokusi pada Poster Iklan Mie Indomie Periode 2019-2020 (Studi Analisis Pragmatik) - Nurul Izzati (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This paper discusses the illocutionary speech acts of the Mie Indomie advertisement poster for the 2019-2020 period which was published on the Indomie Egypt - facebook account. This study focuses on discussing the communicative forms and functions of illocutionary speech acts contained in the Mie Indomie advertising poster for the 2019-2020 period, as well as what speech modes are used when marketing the product. All of the focus of this research will be dissected by using the theory of illocutionary speech acts proposed by Searle. The results showed that during the 2019-2020 period, the Mie Indomie company launched 18 advertising posters. Where out of these 18 advertisement posters, 12 Mie Indomie advertisement posters use declarative speech mode, 4 advertisement posters use imperative speech mode, and 2 posters use interrogative speech mode. As for the speech function, there are 7 MieIndomie advertising posters that use assertive speech functions, 7 advertising posters that use directive speech functions, and 4 advertising posters that use commissive speech functions with each communicative function.